2009
DOI: 10.1021/es803664x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Nutrient Trends in Streams and Rivers of the United States, 1993−2003

Abstract: Trends in flow-adjusted concentrations (indicators of anthropogenic changes) and observed concentrations (indicators of natural and anthropogenic changes) of total phosphorus and total nitrogen from 1993 to 2003 were evaluated in the eastern, central, and western United States by adapting the Regional Kendall trend test to account for seasonality and spatial correlation. The only significant regional trend was an increase in flow-adjusted concentrations of total phosphorus in the central United States, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
4
49
3
Order By: Relevance
“…Human factors such as implementation of pollution-control strategies (for example, water-treatment improvements) are designed to reduce nutrients reaching streams, but their effects may be offset by changes in streamflow at some sites. The inclusion of all factors affecting concentration, including streamflow, allows trends affecting aquatic ecosystems and the status of the streams relative to water-quality standards to be evaluated for a site (Hirsch and others, 1991;Sprague and others, 2006;Sprague and Lorenz, 2009). …”
Section: Temporal Trend Analysis-methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human factors such as implementation of pollution-control strategies (for example, water-treatment improvements) are designed to reduce nutrients reaching streams, but their effects may be offset by changes in streamflow at some sites. The inclusion of all factors affecting concentration, including streamflow, allows trends affecting aquatic ecosystems and the status of the streams relative to water-quality standards to be evaluated for a site (Hirsch and others, 1991;Sprague and others, 2006;Sprague and Lorenz, 2009). …”
Section: Temporal Trend Analysis-methodsmentioning
confidence: 99%
“…The exclusion of streamflow as a variable affecting concentration allows trends to be identified that reflect changes in the mobilization and transport of nutrients in the basin (rather than at the site) caused by factors other than streamflow (Schertz and others, 1991;Sprague and others, 2006;Sprague and Lorenz, 2009). These factors are typically anthropogenic and may include pollution-control strategies (for example, implementation of best-management practices to reduce nutrient runoff from cropland) or factors that may contribute to increased concentrations (for example, increased nutrients in wastewater discharge as a result of increasing population).…”
Section: Temporal Trend Analysis-methodsmentioning
confidence: 99%
“…Trends at individual stations were computed using the Mann-Kendall test and Sen slope estimator, and trends for each mountain group were computed using the RKT. To account for broad-scale climate patterns that might affect precipitation and temperature similarly for a group of stations, the results of the RKT test were corrected for spatial correlation using the method described in Sprague and Lorenz (2009).…”
Section: Climate Datamentioning
confidence: 99%
“…There is a tendency that total phosphorus (TP) in rivers in the central area of the US increases with the substantially increased application of fertilizer (Sprague & Lorenz, 2009). These studies point out that content of phosphorus in aerated soil exceeds the capacity of adsorbing phosphorus due to the extreme agricultural activities and excessive application of phosphatic fertilizer in the above basins, accordingly the surplus phosphorus enters groundwater.…”
Section: Introductionmentioning
confidence: 99%